Koti, hyvinvointityö ja haavoittuvuus - Günther, Kirsi (Tampere University Press, 2022)
In this book [titled Home, welfare work and vulnerability] the authors take the reader on welfare workers' home visits to clients in need of support in their living. Welfare workers refer to professionals in health and social care who in the book are represented among others by social workers, social care workers and nurses. The main concepts of the book are home, welfare work and vulnerability and these are contemplated from different angles. Welfare work entails encountering people who are in vulnerable situations in the midst of their everyday lives. They may need support in coping with their mental health, with physical illnesses, with the challenges of achieving sobriety and recovery or perhaps with the difficulties accompanying old age. On the one hand their ability to act is limited and weak but on the other they have many kinds of strengths and resources. The book addresses a significant turning point in welfare services and work at which the objective is defined as the right of every individual to their own home and making living at home feasible for as long as possible. In the last fifty years or so many societal factors have made possible the dismantling of institutions, the reduction of places and the shortening of stays in institutions, the further development of care in the community, the construction of small residential and care facilities and most recently the further development of services to be taken into people's homes. The last stage of this dismantling of institutions is referred to in the book as the "home turn". As a societal change the home turn is complex - and that is how it is approached in the book. When one's own home is the main place in which welfare policy and work are implemented, it is important to scrutinize more closely what actually occurs there and what special issues are connected to this given context. The book offers a timely point of view on the development of welfare services and the grass-root level welfare work done in the homes. It draws on interaction research based on ethnomethodology and human geography. Research data consist of recordings of home visits, researcher's field diaries and interviews with clients and workers. The work includes both chapters providing conceptual and theoretical overviews and empirical research on the encounters between client and worker(s) on home visits. Welfare work accomplished in people's homes entails many tensions and ethical issues which are analysed in the book and made visible through the means of research.